Dataset: Cyber Law and Piracy: A Comprehensive Analysis of Scholarly Works from 2012-2022 - Kurnia Ningsih Kolopita; Mochammad Tanzil Multazam (International Consortium of Education and Culture Research Studies, 2022)
This data article aims to compile and analyze scholarly works on cyber law and piracy within the legal domain using Lens.org's search and filtering tools. The methodology involves an initial keyword search followed by three filtering stages, narrowing the scope to journal articles published between 2012 and 2022. The analysis highlights the most active authors, institutions, publishers, and countries/regions. Results indicate that University of Louisville, George E Higgins, Springer Nature, and the United States are leading contributors in this field. The findings offer valuable insights for researchers seeking relevant literature on cyber law and piracy in the context of law. Highlights: The study provides a comprehensive overview of scholarly works related to cyber law and piracy in the legal domain, enabling efficient access to relevant literature. The analysis highlights key contributors in the field, including authors, institutions, publishers, and countries/regions, identifying leaders in the domain. The study demonstrates the effectiveness of Lens.org's search and filtering tools in identifying and analyzing relevant scholarly works within specific research areas.